Communication in Social Media: Football Clubs, Language, and Ideology - Papadima, Aspasia; Photiadis, Thomas (My University, 2019)
This article explores the associations between ideology and language in online written communication of football fans in official Facebook groups. The study concentrates on how different Greek-Cypriot political ideologies influence the language use of football fans when they communicate online via social media platforms. From the quantitative and qualitative data collected through content analysis of the online football fans’ comments, we conclude that when it comes to social media communication, both language and orthographic choices are influenced by political ideology and reflect the collective identity of football fans. At the ideological level, language use is tied to broader issues, such as territoriality, Europeanness, and Greekness. The outcomes of the current research will facilitate deeper investigation of the role of the language in social media interaction by linguists, cultural analysts, media psychologists, sociologists, and typographers.